2016
DOI: 10.11646/zootaxa.4067.5.2
|View full text |Cite
|
Sign up to set email alerts
|

A new species of bent-toed gecko, genus Cyrtodactylus Gray, 1827 (Reptilia: Squamata: Gekkonidae), from Jawa Timur Province, Java, Indonesia, with taxonomic remarks on C. fumosus (Müller, 1895)

Abstract: A new species of the gekkonid lizard genus Cyrtodactylus Gray, 1827 is described from Klakah, Lumajang Regency, Jawa Timur Province, Java, Indonesia. Cyrtodactylus klakahensis sp. nov. can be distinguished from all other congeners by the presence of (1) a deep precloacal groove in males, (2) three rows of enlarged precloacofemoral scales, of which the third row bears 37-38 pores in males, (3) three or four rows of enlarged scales between the precloacofemoral scale rows and the cloaca, forming distinct chevrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…), we noticed some inaccuracies in our previously published comparative table (Hartmann et al 2016: Table 3), pertaining largely to the presence/absence of a precloacal depression in males vs. females. We herein correct these inaccuracies and take the opportunity to complement the earlier table by including the recently described Cyrtodactylus hitchi Riyanto, Kurniati &Engilis, 2016 andC.…”
Section: Correction and Update Of The Comparative Table In Hartmann Ementioning
confidence: 65%
See 3 more Smart Citations
“…), we noticed some inaccuracies in our previously published comparative table (Hartmann et al 2016: Table 3), pertaining largely to the presence/absence of a precloacal depression in males vs. females. We herein correct these inaccuracies and take the opportunity to complement the earlier table by including the recently described Cyrtodactylus hitchi Riyanto, Kurniati &Engilis, 2016 andC.…”
Section: Correction and Update Of The Comparative Table In Hartmann Ementioning
confidence: 65%
“…Of pores, grooves, sulci, pits, hollows, and depressions Whereas Kluge (1985) counted 53 pores for the lectotype of Cyrtodactylus marmoratus (RMNH.RENA 2710a.1), we (Hartmann et al 2016) reported 52. We re-examined the specimen and here correct the count to 56 pores, some barely visible.…”
Section: What Constitutes the Entire Type Series?mentioning
confidence: 69%
See 2 more Smart Citations
“…km, and Belitung Island (the type locality of C. purnamai) by ~470 km. The African-Asian Frog genus Chiromantis also occurs in Java (Riyanto & Kurniati 2014;Wostl et al 2017), as do other recently described reptiles and amphibians (Riyanto et al 2014;Hartmann et al 2016;Kieckbusch et al 2016;Wostl et al 2017;Hamidy et al 2018). These novelties have shown Java to be a more herpetologically interesting place than heretofore believed, even though it was believed to have been relatively well studied during the long history of exploration during the Dutch colonial period.…”
Section: Systematicsmentioning
confidence: 83%